2017
DOI: 10.1007/s13365-017-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functioning among HIV-positive adults in southern India

Abstract: The validity of a comprehensive international neuropsychological (NP) test battery for detection of HIV associated neurocognitive disorders (HAND) in a Tamil speaking southern Indian cohort (69 HIV+ and 67 HIV−) was explored. The prevalence of HAND was significantly higher in the HIV+ versus HIV− group (33% vs.13%, p < 0.01). Impairment rates were highest in the motor and speed of information processing domains. An NP battery translated into Tamil appears to be a valid tool for assessing HAND because a prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Some studies showed that compared to clade-B viruses and Tat-B proteins, HIV-1 clade-C and Tat-C induced less cellular inflammation (Gandhi et al, 2009;Kennedy, Petrasca, Doherty, Hennessy, & Spiers, 2014;Yndart et al, 2015) and were less neurovirulent, resulting in lower incidence of HAND (Rao et al, 2008;Satishchandra et al, 2000) and that C31S substitution in Tat-C played a role in these differential inflammation and neurovirulence (Ranga et al, 2004;Rao et al, 2013). However, other studies showed that HAND is prevalent among clade-C-infected subjects (Gupta et al, 2007;Kamat et al, 2017;Tilghman et al, 2014). Studies of demographically similar PLWH showed similar decline in imaging markers of brain integrity (Hoare et al, 2011;Ortega et al, 2013;Paul et al, 2017), similar levels of inflammatory cytokines and chemokines in serum and cerebrospinal fluids (de Almeida et al, 2016), and similar rates of HAND (de Almeida et al, 2013) between clade-B and clade-C infected subjects, independent of Tat C31S substitution (Paul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that compared to clade-B viruses and Tat-B proteins, HIV-1 clade-C and Tat-C induced less cellular inflammation (Gandhi et al, 2009;Kennedy, Petrasca, Doherty, Hennessy, & Spiers, 2014;Yndart et al, 2015) and were less neurovirulent, resulting in lower incidence of HAND (Rao et al, 2008;Satishchandra et al, 2000) and that C31S substitution in Tat-C played a role in these differential inflammation and neurovirulence (Ranga et al, 2004;Rao et al, 2013). However, other studies showed that HAND is prevalent among clade-C-infected subjects (Gupta et al, 2007;Kamat et al, 2017;Tilghman et al, 2014). Studies of demographically similar PLWH showed similar decline in imaging markers of brain integrity (Hoare et al, 2011;Ortega et al, 2013;Paul et al, 2017), similar levels of inflammatory cytokines and chemokines in serum and cerebrospinal fluids (de Almeida et al, 2016), and similar rates of HAND (de Almeida et al, 2013) between clade-B and clade-C infected subjects, independent of Tat C31S substitution (Paul et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These tests have been demonstrated to be sensitive for areas of cognition affected by HIV [26]. The test battery has been used in many international settings related to NP performance in HIV+ participants, in various languages around the world [1 16 2732]. The tests have all been adapted and normed, with demographic corrections for age, sex, education and urban versus rural residence in Zambia [14].…”
Section: Methodsmentioning
confidence: 99%
“…For a priori scenarios, the NeuroHIV research community would need to agree on a core set of neuropsychological tests [35] (e.g. the international HNRC neuropsychological test battery, which has already been adapted and used in different countries, such as China [8], India [10] and Brazil [36]) and a minimum set of data items to be collected provisionally. In both a posteriori and a priori scenarios, a consortium with a steering committee may need to be established to determine how and where the data repository may be developed and maintained.…”
Section: Discussionmentioning
confidence: 99%